Lack of Association of CD36 SNPs With Early Onset Obesity: A Meta‐Analysis in 9,973 European Subjects - Choquet, Hélène; Labrune, Yann; Graeve, Franck; Hinney, Anke; Hebebrand, Johannes; Scherag, André; Lecoeur, Cécile; Tauber, Maithé; Balkau, Beverley; Elliot, Paul; Jarvelin, Marjo‐Riita; Walley, Andrew J.; et al. (Obesity (Silver Spring, Md.), 2011)
A recent study suggested that four CD36 polymorphisms (namely rs3211867, rs3211883, rs3211908, and rs1527483) were associated with an increased risk of obesity, an increased BMI and percentage of body fat in European adolescents. We first attempted to confirm these results in three independent case‐control genome‐wide association studies (GWAS) data totaling 3,509 subjects of French and German origin, but we were unable to find any association of these variants with early onset obesity risk. We then genotyped the four CD36 single‐nucleotide polymorphisms (SNPs) in a large population‐based study of 4,667 Finnish subjects and we did not replicate any of the recently reported associations with BMI. By combining all available data in a meta‐analysis (N = 9,973), we found no evidence for an association of the reported four variants in CD36 with increased obesity risk or increased BMI (0.07 ≤ P values ≤ 0.93). Finally, we assessed the contribution of the full CD36 locus gene variation to obesity risk in 3,509 subjects and we did not detect any significant association with obesity after correction for multiple testing. In summary, we were unable to confirm the recently reported association of variants in CD36 with early onset obesity in populations of European ancestry.